Improved adhesive resins
By using the adhesive resin prepared by the use of lignin and carbohydrates and polyamine reactions, the alternative problem of phenol-formaldehyde type adhesives in the insulating material manufacture is solved, and the effect of high humidity intensity and rapid solidification can be achieved. Essence
Patent Information
- Application Number
- CN202380041206.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-19
- Filing Date
- 2023-05-17
- Publication Date
- 2025-01-28
AI Technical Summary
The prior art is difficult to find a method to replace phenol-formaldehyde type adhesives when manufacturing insulating materials, and existing alternatives have shortcomings in performance and reaction rates.
By using lignin and carbohydrates and polyamine reactions, lignin is provided in the form of ammonia and/or organic alkali water solution to improve reaction and performance.
This method significantly improves the humidity of the adhesive resin, is suitable for the manufacture of insulating materials, and avoids the use of formaldehyde, reducing the dependence on petroleum resources.
Smart Images

Figure GDA0005218004680000121 
Figure GDA0005218004680000131 
Figure GDA0005218004680000132
Abstract
Description
Technical Field
[0001] The present invention relates to a binding resin which can be used, for example, in the manufacture of insulation materials such as mineral wool insulation or glass wool insulation. The present invention also relates to a process for preparing the binding resin and to its use. Background Art
[0002] Adhesive resins can be used to manufacture articles because they can bind together non-assembled or loosely assembled materials. For example, adhesive resins enable two or more surfaces to be united. In particular, adhesive resins can be used to produce products comprising consolidated fibers. Thermosetting adhesive resins can be characterized in that they are converted into insoluble and infusible materials by either heating or catalysis. Examples of thermosetting adhesive resins include various phenol-aldehydes, urea-aldehydes, melamine-aldehydes and other condensation-polymerization materials like furan and polyurethane resins. Adhesive resins containing phenol-aldehydes, resorcinol-aldehydes, phenol / aldehyde / urea, phenol / melamine / aldehydes etc. are used for the bonding of fibers, fabrics, plastics, rubbers and many other materials.
[0003] The mineral wool and fiberboard industries have historically used phenol-formaldehyde binder resins to bind the fibers. Phenol-formaldehyde type binder resins provide suitable properties for the final product; however, environmental considerations have stimulated the development of alternative binders. One such alternative binder resin is a carbohydrate-based binder derived from reacting a carbohydrate with a polyprotic acid, for example according to US2007 / 0027283 and WO2009 / 019235. Another alternative binder resin is the esterification product of a polycarboxylic acid reacted with a polyol, for example according to US2005 / 0202224. Because these binders do not utilize formaldehyde as a reagent, they have been collectively referred to as formaldehyde-free binders.
[0004] One area of development is to find substitutes for phenol-formaldehyde type adhesives across the entire range of products (e.g., fiberglass insulation, particleboard, office panels, and acoustic sound insulation) that use phenol-formaldehyde type adhesives. In particular, previously developed formaldehyde-free adhesive resins may not have all the desired properties for all products. For example, adhesives based on acrylic acid and poly(vinyl alcohol) have shown promising performance characteristics. However, these are relatively more expensive than phenol-formaldehyde adhesives, are substantially derived from petroleum-based resources, and have a tendency to exhibit lower reaction rates (either requiring longer curing times or requiring increased curing temperatures) compared to phenol-formaldehyde-based adhesive resins. Carbohydrate-based adhesive resins are made from relatively inexpensive precursors and are primarily derived from renewable resources; however, these adhesive resins may also require reaction conditions for curing that are substantially different from those under which traditional phenol-formaldehyde adhesive systems are cured. Therefore, it is not yet readily achievable to replace phenol-formaldehyde type adhesives with existing substitutes.
[0005] EP2566904 relates to adhesive formulations comprising the reaction product of a carbohydrate reactant and a polyamine and materials made using the same.
[0006] Lignin, an aromatic polymer, is the main component of wood, and is the most abundant carbon source on Earth after cellulose. In recent years, with the development and commercialization of technologies to extract highly purified, solid and particularized forms of lignin from pulping processes, it has attracted great attention as a possible renewable alternative to the main aromatic chemical precursors currently derived from the petrochemical industry.
[0007] Lignin, a polyaromatic network structure, has been extensively studied as a suitable substitute for phenol during the production of phenol-formaldehyde adhesives. These are used during the manufacture of laminates and structural wood products such as plywood, oriented strand board and fiberboard. During the synthesis of such adhesives, phenol (which can be partially replaced by lignin) reacts with formaldehyde in the presence of either alkaline or acidic catalysts to form highly cross-linked aromatic resins, known as novolacs (when utilizing acidic catalysts) or resols (when utilizing alkaline catalysts). Currently, only a limited amount of phenol can be replaced by lignin due to the lower reactivity of lignin.
[0008] A particular problem in preparing insulation products is obtaining a suitable balance between dry and wet strength properties, which depends largely on the binder resin used. If the insulation product is intended for use in applications where it is exposed to moisture or water, such as for outdoor use, a binder resin must be used which provides sufficient wet strength. Summary of the invention
[0009] It has now surprisingly been found that a binding resin suitable for use in the production of insulating materials can be readily prepared wherein the use of formaldehyde can be avoided. It has also been found that the binding resin provides improved wet strength properties making it particularly useful in the manufacture of insulating materials.
[0010] Further, it has been found that when lignin is provided in the form of an aqueous solution containing ammonia and / or an organic base, the phenolic hydroxyl groups in the lignin structure are deprotonated and are free to react with other components of the binder resin. This improves the reactivity and performance of the binder. Therefore, when manufacturing, for example, mineral wool insulation or glass wool insulation, providing lignin in the form of an aqueous solution containing ammonia and / or an organic base significantly accelerates the reaction rate and thus promotes the curing of the binder resin.
[0011] Furthermore, by providing the lignin in the form of an aqueous solution comprising ammonia and / or an organic base, the risk of degrading eg glass wool and mineral wool fibers is minimized.
[0012] The present invention thus relates to a binding resin comprising the reaction product of a carbohydrate reactant, lignin and a polyamine, wherein the carbohydrate reactant is selected from a monosaccharide, a disaccharide or an oligosaccharide, and wherein the polyamine is a primary polyamine selected from a diamine, a triamine, a tetraamine and a pentamine, and wherein the polyamine is H2N-Q-NH2, wherein Q is C1-C 10 Alkyl, cycloalkyl, C1-C 10 heteroalkyl or cycloheteroalkyl, each of which is optionally substituted; and wherein the lignin is provided as a solution, and wherein the weight ratio of the carbohydrate and the polyamine is in the range of from 1:100 to 100:1, and wherein the weight ratio of the lignin and the carbohydrate is between 1:100 and 100:1, calculated on a dry lignin and dry carbohydrate basis, and wherein the amount of lignin in the binding resin is in the range of from 5 wt % to 30 wt %, calculated on a dry lignin and dry binding resin basis.
[0013] The invention also relates to a fibrous insulation product comprising a binding resin according to the invention. DETAILED DESCRIPTION
[0014] Throughout this specification, the expression "lignin" is intended to encompass any kind of lignin, such as lignin derived from hardwood, softwood or annular plants. Preferably, the lignin is an alkaline lignin generated in, for example, a Kraft process. Preferably, the lignin has been purified or separated before being used in the process according to the present invention. Lignin can be separated from black liquor and optionally further purified before being used in the process according to the present invention. Purification typically makes the purity of lignin at least 90%, preferably at least 95%. Thus, the lignin used according to the method of the present invention preferably contains less than 10%, preferably less than 5% impurities. Lignin can then be separated from black liquor using a process disclosed in WO2006031175. Lignin can then be separated from black liquor using a process called LignoBoost process. Lignin can be provided in the form of particles, such as particles with an average particle size from 50 microns to 500 microns. Lignin can also be provided in the form of agglomerates, the agglomerates having an average diameter from 0.01 to 10 mm, such as from 0.1 to 5 mm.
[0015] The reactivity of lignin can be increased by modifying the lignin via glyoxylation, etherification, esterification, amination or any other method that increases the hydroxyl content or carboxyl content or amine content or thiol content of the lignin. Preferably, the lignin used according to the present invention is not chemically modified after it is extracted and separated from wood. More specifically, the lignin is preferably not subjected to oxidation after it has been separated from the kraft process.
[0016] The aqueous solution of lignin containing ammonia and / or an organic base can be prepared by methods known in the art, for example, by mixing lignin and ammonia and / or an organic base with water. The pH of the aqueous solution of lignin containing ammonia and / or an organic base is preferably in the range of from 8 to 14, more preferably in the range of from 9 to 11 or 10 to 11. Examples of organic bases include amines, such as primary amines, secondary amines and tertiary amines and mixtures thereof. Preferably, the organic base is selected from methylamine, ethylamine, propylamine, butylamine, ethylenediamine, methanolamine, ethanolamine, aniline, cyclohexylamine, benzylamine, dimethylamine, diethylamine, dipropylamine, dibutylamine, dimethanolamine, diethanolamine, diphenylamine, benzylamine, phenylethylamine, hexamethylenediamine, polyetheramine, dicyclohexylamine, piperazine, imidazole, 2-methylimidazole, 2-ethylimidazole, 2-ethyl-4-methylimidazole, 2-isopropylimidazole, 2-phenylimidazole, 2-methylimidazoline, 2-phenylimidazoline, trimethylamine, triethylamine, dimethylhexylamine, N-methylpiperazine, dimethylbenzylamine, aminomethylpropanol, tris(dimethylaminomethyl)phenol and dimethylaniline and mixtures thereof. The total amount of ammonia and / or organic base in the aqueous solution is preferably in the range of 0.1% to 20% by weight, preferably 0.1% to 10% by weight of the total weight of the aqueous solution containing water, lignin and ammonia and / or organic base. The amount of lignin in the aqueous solution containing ammonia and / or organic base is preferably from 1% to 60% by weight of the solution, such as from 10% to 30% by weight of the solution. The aqueous solution containing ammonia and / or organic base lignin contains less than 1% by weight alkali and less than 1% by weight inorganic base. More preferably, the aqueous solution containing ammonia and / or organic base lignin does not contain alkali and does not contain inorganic base.
[0017] The amount of lignin in the binding resin is preferably from 5% by weight to 50% by weight, calculated based on the dry weight of lignin and the total weight of the binding resin.
[0018] As used herein, polyamines are organic compounds with two or more amine groups. As used herein, primary polyamines are organic compounds with two or more primary amine groups (-NH2). Within the scope of the term primary polyamines are those compounds that can be in situ modified or isomerized to generate compounds with two or more primary amine groups (-NH2). Polyamines are primary polyamines.
[0019] The polyamine used in the adhesive resin according to the present invention may be a molecule having the formula H2N-Q-NH2, wherein Q is an alkyl, cycloalkyl, heteroalkyl or cycloheteroalkyl group, each of which may be optionally substituted. 24In one embodiment, Q is an alkyl group selected from C2-C8 alkyl groups. In one embodiment, Q is an alkyl group selected from C3-C7 alkyl groups. In one embodiment, Q is a C6 alkyl group. In one embodiment, Q is selected from cyclohexyl, cyclopentyl or cyclobutyl. In one embodiment, Q is benzyl.
[0020] As used herein, the term "alkyl" includes a chain of carbon atoms, which is optionally branched. It should be further understood that the alkyl group advantageously has a limited length, including C1-C 24 、C1-C 12 , C1-C8, C1-C6 and C1-C4. It will be appreciated that shorter alkyl, alkenyl and / or alkynyl groups herein may add less hydrophilicity to the compound and accordingly will have different reactivity to the carbohydrate reactant and solubility in the binder solution.
[0021] As used herein, the term "cycloalkyl" includes a chain of carbon atoms, which is optionally branched, wherein at least a portion of the chain is cyclic. It should be understood that cycloalkylalkyl is a subset of cycloalkyl. It should be understood that cycloalkyl can be polycyclic. Exemplary cycloalkyls include, but are not limited to, cyclopropyl, cyclopentyl, cyclohexyl, 2-methylcyclopropyl, cyclopentylethyl-2-yl, adamantyl, and the like. It will be further understood that the chain forming the cycloalkyl advantageously has a limited length, including C3-C 24 、C3-C 12 , C3-C8, C3-C6 and C5-C6. It is understood herein that shorter alkyl chains forming the cycloalkyl group may add less lipophilicity to the compound and accordingly will behave differently.
[0022] As used herein, the term "heteroalkyl" includes a chain of atoms including carbon and at least one heteroatom, and is optionally branched. Exemplary heteroatoms include nitrogen, oxygen and sulfur. In some variants, exemplary heteroatoms also include phosphorus and selenium. In one embodiment, heteroalkyl is a polyether. As used herein, the term "cycloheteroalkyl" including heterocyclic radicals and heterocycles includes a chain of atoms including carbon and at least one heteroatom, such as heteroalkyl, and is optionally branched, wherein at least a portion of the chain is cyclic. Exemplary heteroatoms include nitrogen, oxygen and sulfur. In some variants, exemplary heteroatoms also include phosphorus and selenium. Exemplary cycloheteroalkyl includes but is not limited to tetrahydrofuranyl, pyrrolidinyl, tetrahydropyranyl, piperidinyl, morpholinyl, piperazinyl, homopiperazinyl, quinuclidinyl, etc.
[0023] As used herein, the term "optionally substituted" includes replacing hydrogen atoms with other functional groups on the optionally substituted group. Such other functional groups illustratively include, but are not limited to, amino, hydroxyl, halogen, thiol, alkyl, halogen alkyl, heteroalkyl, aryl, aralkyl, aryl heteroalkyl, nitro, sulfonic acid and derivatives thereof, carboxylic acid and derivatives thereof, etc. Exemplarily, any amino, hydroxyl, thiol, alkyl, halogen alkyl, heteroalkyl, aryl, aralkyl, aryl heteroalkyl and / or sulfonic acid is optionally substituted.
[0024] In one embodiment of the present invention, the polyamine is selected from diamines, triamines, tetramines and pentamines. In one embodiment, the polyamine is a diamine selected from 1,6-diaminohexane, 1,5-diamino-2-methylpentane and 3-(aminomethyl)-3,5,5-trimethylcyclohexane-1-amine. In one embodiment, the diamine is 1,6-diaminohexane. In one embodiment, the polyamine is a triamine selected from diethylenetriamine, 1-piperazineethaneamine and bis(hexamethylene)triamine. In one embodiment, the polyamine is a tetraamine such as triethylenetetramine. In one embodiment, the polyamine is a pentamine such as tetraethylenepentamine. In one embodiment, the primary polyamine is a polyether-polyamine. In one embodiment, the polyether-polyamine is a diamine or a triamine.
[0025] The carbohydrate reactant is a monosaccharide, a disaccharide or an oligosaccharide. In one embodiment, the carbohydrate is a monosaccharide in its aldose or ketose form. In one embodiment, the carbohydrate may be a reducing sugar. In one embodiment, the carbohydrate reactant is selected from glucose, xylose, fructose, dihydroxyacetone and mixtures thereof. In one embodiment, the carbohydrate reactant is a disaccharide such as sucrose, lactose or maltose. In one embodiment, the carbohydrate reactant is an oligosaccharide such as chitosan.
[0026] The weight ratio of carbohydrate to polyamine is in the range of from 1:100 to 100:1, calculated on a dry solids basis. Preferably, the weight ratio of carbohydrate reactant to polyamine is in the range of from 20:1 to 1:20, and more preferably in the range of from 10:1 to 1:10, or most preferably in the range of from 1:5 to 5:1, or in the range of from 1:1.1 to 1.1:1, calculated on a dry solids basis.
[0027] The weight ratio of lignin to carbohydrates, calculated on a dry lignin and dry carbohydrate basis, is between 100:1 and 1:100, preferably in the range of 20:1 and 1:20, and more preferably in the range of from 10:1 to 1:10, or in the range of from 6:1 to 1:1, calculated on a dry solids basis.
[0028] The weight ratio of lignin to polyamine, calculated on a dry lignin and dry carbohydrate basis, is between 100:1 and 1:100, preferably in the range of 20:1 and 1:20, and more preferably in the range of from 10:1 to 1:10, or in the range of from 6:1 to 1:1, calculated on a dry solids basis.
[0029] The solid content of the adhesive resin before curing is preferably in the range from 10% to 70%, such as in the range from 15% to 50%.
[0030] The adhesive resin may also include additives such as urea, tannin, surfactant, dispersant and filler. The adhesive resin may also include plasticizer. In one embodiment, the adhesive resin does not include plasticizer. As used herein, the term "plasticizer" refers to such an agent, when added to lignin, by reducing the glass transition temperature (Tg) and improving its flow behavior, lignin is made softer and more flexible to improve its plasticity. The example of plasticizer includes polyol, alkyl citrate (salt), organic carbonate (salt), phthalate (salt), adipate (salt), sebacate (salt), maleate (salt), benzoate (salt), trimellitate (salt) and organic phosphate (salt). Polyol includes for example polyethylene glycol, polypropylene glycol, glycerol, diglycerol, polyglycerol, butanediol, sorbitol and polyvinyl alcohol. Alkyl citrate includes for example triethyl citrate, tributyl citrate, acetyl triethyl citrate and trimethyl citrate.
[0031] Organic carbonates include, for example, ethylene carbonate, propylene carbonate, glycerol carbonate, and vinyl carbonate. Further examples of plasticizers include polyethylene glycol ethers, polyethers, hydrogenated sugars, triacetin, and solvents used as coalescing agents such as alcohol ethers. In one embodiment of the invention, the plasticizer is a polyol, such as a polyol selected from polyethylene glycol and polypropylene glycol. If the resin includes a plasticizer, the weight ratio between the plasticizer and the lignin is preferably from 0.1:10 to 10:1, calculated on the basis of the dry weight of each component. Preferably, the weight ratio between the plasticizer (if present) and the lignin is from 0.1:10 to 10:10, such as from 1:10 to 5:10, calculated on the basis of the dry weight of each component. The adhesive resin may also include a coupling agent. The coupling agent is, for example, a silane-based coupling agent. In one embodiment, the adhesive resin does not include a coupling agent.
[0032] Fillers and / or hardeners may also be added to the binding resin. Examples of such fillers and / or hardeners include limestone, cellulose, sodium carbonate and starch. In one embodiment, the binding resin does not contain fillers and / or hardeners.
[0033] Preferably, the binding resin according to the invention does not contain formaldehyde. Preferably, the binding resin does not contain phenol.
[0034] Preferably, the binder resin according to the present invention does not contain a basic catalyst. Further, preferably, no basic catalyst is used in the production of the binder resin according to the present invention.
[0035] In one embodiment of the present invention, no epoxy-based crosslinking agent is used in the bonding resin.
[0036] Cellulosic materials used according to the present invention are, for example, mineral fibers (glass fibers, slag wool fibers and rock wool fibers), aramid fibers, ceramic fibers, metal fibers, carbon fibers, polyimide fibers, certain polyester fibers and rayon fibers. Such fibers are substantially unaffected by exposure to temperatures above about 120° C. In one embodiment, the insulating fibers are glass fibers. In one embodiment, the mineral fibers are present in the insulation product according to the present invention in the range from about 70% to about 99% by weight.
[0037] In one embodiment, the cellulosic material comprises cellulose fibers. For example, the cellulose fibers may be wood chips, sawdust, wood pulp, or milled wood. In one embodiment, the cellulose fibers may be other natural fibers such as jute, flax, hemp, and straw.
[0038] As used herein, the term adhesive solution is a solution of chemicals that can be substantially dehydrated to form an uncured adhesive resin. As used herein, the adhesive resin can be cured, uncured or partially cured. The composition of the uncured adhesive resin is called an uncured adhesive resin. The uncured adhesive resin is a substantially dehydrated mixture of chemicals that can be cured to form a cured adhesive resin. Substantially dehydrated means that the solvent (typically water or a mixture thereof) used to make the adhesive solution is evaporated to a sufficiently high degree that the viscosity of the remaining material (comprising the adhesive reactant and the solvent) is sufficiently high to produce cohesion between the loosely assembled substances; thus, the remaining material is an uncured adhesive resin. In one embodiment, the solvent is less than 65% of the total weight of the remaining material. In one embodiment, the substantially dehydrated adhesive resin has a moisture content of water between about 5% by weight and about 65% by weight of the total adhesive. In one embodiment, the solvent may be less than 50% of the total weight of the remaining material. In one embodiment, the solvent may be less than 35% of the total weight of the remaining material. In one embodiment, the substantially dehydrated binding resin has between about 10% and about 35% water by weight of the total binding resin. In one embodiment, the solvent may comprise less than about 20% of the total weight of the remaining materials.
[0039] As used herein, the term cured adhesive resin describes the polymer product of curing uncured adhesive resin. Cured adhesive resin can have characteristic brown to black. Although described as brown or black, the additional feature is that the adhesive tends to absorb light in a wide range of wavelengths. Since the polymer of the cured adhesive resin is widely cross-linked, the cured adhesive resin is substantially insoluble. For example, the adhesive resin is mainly insoluble in water. As described herein, uncured adhesive resin provides sufficient bonding ability to consolidate the fibers; however, the cured adhesive resin imparts firmness, long-lasting durability and physical properties conventionally associated with cross-linked polymers.
[0040] The binder resin reactants described herein are soluble in water, and when combined in water, a binder solution is obtained. In one embodiment, a surfactant is included in the aqueous solution to improve the solubility or dispersibility of one or more binder resin reactants or additives. For example, a surfactant can be added to the binder aqueous solution to enhance the dispersibility of the particulate additive. In one embodiment, a surfactant is used to produce an emulsion with a non-polar additive or binder reactant. In one embodiment, the binder solution includes about 0.01% by weight to about 5% by weight of a surfactant, based on the weight of the binder solution.
[0041] During the production of the fibrous insulation product, the binder solution described herein can be applied to the fibrous material (e.g., sprayed onto the mat or onto the fibers as it enters the forming area). When the binder solution contacts the mineral fibers, the residual heat from the mineral fibers (note that, for example, glass fibers are made of molten glass and thus contain residual heat) and the flow of air through and / or around the product will cause a portion of the water to evaporate from the binder solution. Removal of the water leaves the remaining components of the binder resin on the fibers as a coating of a viscous or semi-viscous high solids mixture. The coating of the viscous or semi-viscous high solids mixture acts as a binder resin. At this point, the mat is still uncured. In other words, the uncured binder resin acts to bind the fibers in the mat.
[0042] The uncured binder resin described above may be cured. For example, the process of making a cured insulation product may include a subsequent step in which heat is applied to cause a chemical reaction in the uncured binder resin. For example, in the case of making a glass fiber insulation product or other mineral fiber insulation product, after the binder solution has been applied to the fibers and dehydrated, the uncured insulation product may be transferred to a curing oven. The uncured insulation product is heated in the curing oven (e.g., from about 150° C. to about 320° C.) so that the binder resin is cured. The binder resin thus cured is a formaldehyde-free, waterproof binder resin that binds the fibers of the fibrous insulation product together. Drying and heat curing may occur either sequentially, simultaneously, contemporaneously, or concurrently.
[0043] The uncured fiber product typically comprises from about 3% to about 40% by weight dry binder solids (total uncured solids). In one embodiment, the uncured fiber product comprises from about 5% to about 25% dry binder solids. In one embodiment, the uncured fiber product comprises from about 50% to about 97% by weight fibers.
[0044] Cured adhesive resin is the product that makes adhesive resin solidify.Term curing indicates that adhesive resin has been exposed to the condition that causes chemical change.The example of these chemical changes may include but is not limited to, (i) covalent bonding, (ii) hydrogen bonding of adhesive component, and (iii) polymer and / or oligomer chemical crosslinking in adhesive resin.Compared with uncured adhesive resin, these changes can improve the durability and solvent resistance of adhesive resin.Curing adhesive resin can obtain the formation of thermosetting material.In addition, compared with uncured adhesive resin, curing adhesive resin can obtain the improvement of adhesion between materials in the set.Curing can be caused by one or more conditions of for example heat, microwave radiation and / or causing the chemical change mentioned above.
[0045] In cases where chemical changes in the binding resin result in the release of water, such as polymerization and cross-linking, curing can be determined by the amount of water released being above that which would occur from drying alone. Techniques for measuring the amount of water released during drying compared to when curing the binding resin are well known in the art.
[0046] Example
[0047] Example 1 - Preparation of lignin-ammonia solution
[0048] The lignin ammonia solution was prepared by first adding 211 g of powdered lignin (95% solids when measured using a laboratory infrared moisture analyzer) and 685 g of water to a 1 L glass reactor at room temperature and stirring until the lignin was completely and evenly dispersed. Subsequently, 104 g of a 28-30% ammonia solution was added to the lignin dispersion. The composition was stirred for 60 minutes to ensure complete dissolution of the lignin.
[0049] Example 2 - Preparation of lignin-ammonia solution with plasticizer.
[0050] The lignin-ammonia solution with plasticizer is prepared by adding 211g of powdered lignin (95% solid content when measured using a laboratory infrared moisture analyzer), 685g of water and 50g of PEG400 to a 1L glass reactor at room temperature, and stirring until the lignin is completely and evenly dispersed. Subsequently, 104g of 28-30% ammonia solution is added to the lignin dispersion. The composition is stirred for 60 minutes to ensure complete dissolution of the lignin.
[0051] Example 3 - Preparation of glass rod samples for mechanical testing
[0052] If necessary, the binder solution was diluted with water and combined with a 1% solution of 3-aminopropyltrimethoxysilane (APTES) in water to obtain a final solution with a total concentration of 20-23% (total DS) and a concentration of 0.5% APTES.
[0053] The adhesive was mixed with spherical glass beads (Sibelco The granules (average size 300-400 μm) were combined and stirred thoroughly using a spatula to obtain a paste of uniform thickness with a binder-on-glass concentration of 4%.
[0054] The paste was transferred to a silicone mold consisting of 8 identical rectangular cavities with a length of 215 mm, a width of 107 mm, and a thickness of 16 mm.
[0055] The paste was evenly distributed among all 8 cavities and the silicone mold was transferred to an oven and subjected to heating at 200°C for 60 min.
[0056] After heating, the mold was allowed to cool to room temperature and 8 identical solid sticks were separated from the mold and stored for further analysis.
[0057] Example 4 - Mechanical Properties of Glass Rod Samples
[0058] The mechanical properties of the glass rods were measured in terms of dry strength (strength of a dry glass rod) and wet strength (strength of a glass rod after conditioning at 80° C. in water for 2 h).
[0059] For dry strength and wet strength, the glass rods were divided into two groups. The samples for dry strength were analyzed as they were. The samples for wet strength were analyzed immediately after conditioning at 80° C. in water for 2 h.
[0060] The weight of the sample before and after conditioning is obtained to measure the water absorption of the sample.
[0061] Strength is measured as follows: Use a caliper to obtain the dimensions of the glass rod. Mount the glass rod on a 65 mm support fixture consisting of two anvils, equally spaced from the center point. Slowly lower the upper anvil to the center point at a constant rate. Record the force at the breaking point of the specimen and convert it to strength at break using the dimensions of the rod.
[0062] Example 5 - Comparative Example 1
[0063] A solution consisting of 14 g glucose, 6 g hexamethylenediamine (HMDA), 8.3 g ammonia solution (28-30% strength) and 51.7 g water was prepared to obtain a binder having 28% dry solids and a carbohydrate-polyamine ratio of 70:30 (based on weight).
[0064] The composition was heated at 50°C for 20 min to ensure complete dissolution of all components.
[0065] After this, glass rods were prepared and analyzed as described in Examples 3 and 4.
[0066] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0067] Dry strength(MPa) Wet strength (MPa) difference 7.1 1.1 -84.5%
[0068] Example 6 - Comparative Example 2
[0069] A solution consisting of 10 g glucose, 10 g hexamethylenediamine (HMDA), 8.3 g ammonia solution (28-30% strength) and 51.7 g water was prepared to obtain a binder having 28% dry solids and a carbohydrate-polyamine ratio of 50:50 (based on weight).
[0070] The composition was stirred for 20 min to ensure complete dissolution of all components.
[0071] After this, glass rods were prepared and analyzed as described in Examples 3 and 4.
[0072] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0073] Dry strength(MPa) Wet strength (MPa) difference 9.0 1.2 -86.8%
[0074] Example 7 - Comparative Example 3
[0075] A solution consisting of 5 g hexamethylenediamine (HMDA) in 5 g water was prepared to obtain a polyamine solution with 50% dry solids. The polyamine solution was mixed with 50 g of lignin-ammonia-plasticizer solution to obtain a lignin-polyamine adhesive with 25% total dry solids.
[0076] The finished adhesive was used for glass rod preparation and analysis as described in Examples 3 and 4.
[0077] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0078] Dry strength(MPa) Wet strength (MPa) difference 2.21 2.13 -3.6%
[0079] Example 8
[0080] A solution of 12.6 g glucose and 5.4 g hexamethylenediamine (HMDA) and 14 g water was prepared to obtain a carbohydrate-polyamine ratio of 70:30 (based on weight) and 60% dry solids. The composition was stirred for 20 min to ensure complete dissolution of all components. The final composition was identified as "Component A".
[0081] This solution was combined with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0082] Adhesive No. Component A(g) Component B(g) 8.1 6.8 68.0 8.2 11.0 55.0 8.3 16.0 40.0
[0083] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0084] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0085] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 8.1 2.5 4.1 +62.9% 8.2 3.5 4.6 +32.8% 8.3 6.2 4.7 -24.3%
[0086] Example 9
[0087] A solution of 10.5 g glucose and 10.5 g hexamethylenediamine (HMDA) and 14 g water was prepared to obtain a 50:50 carbohydrate-polyamine ratio (based on weight) and 60% dry solids. The composition was stirred for 20 min to ensure complete dissolution of all components. The final composition was identified as "Component A".
[0088] This solution was combined with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0089]
[0090]
[0091] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0092] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0093] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 9.1 3.4 4.9 +47.2% 9.2 3.7 4.9 +33.3% 9.3 4.5 3.9 -14.4%
[0094] Example 10
[0095] A solution of 8.4 g glucose and 12.6 g hexamethylenediamine (HMDA) and 14.0 g water was prepared to obtain a carbohydrate-polyamine ratio of 40:60 (based on weight) and 60% dry solids. The composition was stirred for 20 min to ensure complete dissolution of all components. The final composition was identified as "Component A".
[0096] This solution was combined with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0097] Adhesive No. Component A(g) Component B(g) 10.1 6.8 68.0 10.2 11.0 55.0 10.3 16.0 40.0
[0098] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0099] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0100]
[0101]
[0102] Embodiment 11
[0103] A series of carbohydrate-polyamine compositions were prepared with a carbohydrate-polyamine ratio of 60:40 (on a dry weight basis) and a dry solids of 60% (on a dry weight basis) as follows:
[0104]
[0105] The polyamine designated "IPDA" is 3-(aminomethyl)-3,5,5-trimethylcyclohexane-1-amine.
[0106] Compositions 11.1 to 11.5 were stirred for 20 min to ensure complete dissolution of all components.
[0107] Each of compositions 11.1 to 11.5 (identified as "component A") was used to prepare the final adhesive by combining with a lignin-ammonia-plasticizer solution (identified as "component B") in the following amounts:
[0108] Adhesive No. Component A(g) Component B(g) 11.1 11.0 55.0 11.2 11.0 55.0 11.3 11.0 55.0 11.4 11.0 55.0 11.5 11.0 55.0
[0109] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0110] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0111] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 11.1 2.3 2.2 -5.7% 11.2 4.8 4.8 -0.6% 11.3 3.4 3.1 -6.6% 11.4 7.4 6.5 -11.3% 11.5 2.5 2.1 -16.7%
[0112] Example 12
[0113] A series of carbohydrate-polyamine compositions were prepared as follows, wherein the dry solids were 60% (on a dry weight basis):
[0114]
[0115] The polyamine labeled "J-ED600" is an O,O'-bis(2-aminopropyl)polypropylene glycol-block-polyethylene glycol-block-polypropylene glycol derivative.
[0116] The polyamine designated as "TETA" is triethylenetetramine.
[0117] Compositions 12.1 to 12.4 were stirred for 20 min to ensure complete dissolution of all components.
[0118] Each of the compositions (identified as "Component A") was used to prepare the final adhesive by combining with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0119]
[0120]
[0121] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0122] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0123] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 12.1 2.9 2.3 -18.6% 12.2 2.7 2.1 -21.3% 12.3 2.5 3.0 +18.5% 12.4 2.1 1.5 -26.7%
[0124] Embodiment 13
[0125] Two mixed carbohydrate-polyamine compositions were prepared with a total carbohydrate-polyamine ratio of 70:30 (on a dry weight basis) and 60% dry solids (on a dry weight basis) by combining:
[0126]
[0127] Composition 12.1 was stirred at room temperature for 20 min to ensure complete dissolution of all components.
[0128] Composition 12.1 was heated at 50°C for 20 min to ensure complete dissolution of all components.
[0129] The composition (identified as "Component A") was further used to prepare the final adhesive by combining with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0130] Adhesive No. Component A(g) Component B(g) 13.1 11.0 55 13.2 11.0 55
[0131] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0132] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0133] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 13.1 3.7 5.0 +35.5% 13.2 3.3 4.1 +23.4%
[0134] Embodiment 14
[0135] Two mixed carbohydrate-polyamine compositions were prepared with a total carbohydrate-polyamine ratio of 60:40 (on a dry weight basis) and 60% dry solids (on a dry weight basis) by combining:
[0136]
[0137] Composition 14.1 was stirred at room temperature for 20 min to ensure complete dissolution of all components.
[0138] Composition 14.2 was heated at 50°C for 20 min to ensure complete dissolution of all components.
[0139] The composition (identified as "Component A") was further used to prepare the final adhesive by combining with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0140]
[0141]
[0142] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0143] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0144] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 14.1 4.4 5.0 +13.6% 14.2 4.2 4.4 +4.8%
[0145] Embodiment 15
[0146] A solution consisting of 17.5 g glucose, 7.5 g hexamethylenediamine (HMDA), 10.4 g ammonia solution (28-30% strength) and 64.6 g water was prepared to obtain a binder having 28% dry solids and a carbohydrate-polyamine ratio of 70:30 (based on weight).
[0147] The composition was stirred for 20 min to ensure complete dissolution of all components. The final composition was identified as "Component A".
[0148] This solution was combined with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0149] Adhesive No. Component A(g) Component B(g) 15.1 54 5.4 15.2 45 18
[0150] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0151] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0152]
[0153]
[0154] Example 16
[0155] A solution consisting of 10 g glucose, 15 g hexamethylenediamine (HMDA), 10.4 g ammonia solution (28-30% strength) and 64.6 g water was prepared to obtain an adhesive having 28% dry solids and a carbohydrate-polyamine ratio of 40:60 (based on weight).
[0156] The composition was stirred for 20 min to ensure complete dissolution of all components. The final composition was identified as "Component A".
[0157] This solution was combined with a lignin-ammonia-plasticizer solution (identified as "Component B") in the following amounts:
[0158] Adhesive No. Component A(g) Component B(g) 16.1 54 5.4 16.2 45 18
[0159] The finished adhesive was then used for glass rod preparation and analysis as described in Examples 3 and 4.
[0160] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0161] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 15.1 6.2 2.9 -53.1% 15.2 4.7 2.5 -46.7%
[0162] Embodiment 17
[0163] A solution consisting of 2.8 g glucose, 2.4 g maltose and 5.2 g H2O was prepared and stirred until completely dissolved. This solution was identified as "Component A".
[0164] Prepare a solution of 3.6 g hexamethylenediamine (HMDA) and 3.6 g H2O and stir until completely dissolved. This solution is identified as "Component B".
[0165] The compositions identified as "Component A" and "Component B" were combined with a lignin-ammonia-plasticizer solution (identified as "Component C") in the following amounts:
[0166]
[0167]
[0168] The adhesive was used immediately (within 1-2 minutes) for glass rod preparation and analysis as described in Examples 3 and 4.
[0169] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0170] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 17 3.7 4.2 +13.5%
[0171] Embodiment 18
[0172] A solution consisting of 60 g of lignin-ammonia-plasticizer solution, 2.3 g of glucose and 2.0 g of maltose was prepared and stirred until completely dissolved. This solution was identified as "Component A".
[0173] Prepare a solution of 2.9 g hexamethylenediamine (HMDA), 9.6 g H2O and stir until completely dissolved. This solution is identified as "Component B".
[0174] Combine the compositions identified as "Component A" and "Component B" in the following amounts:
[0175] Adhesive No. Component A(g) Component B(g) 18 50 10
[0176] The adhesive was used immediately (within 1-2 minutes) for glass rod preparation and analysis as described in Examples 3 and 4.
[0177] The mechanical strengths obtained (dry and wet) and the difference between the two (in percent, relative to the dry strength) are tabulated below. A negative difference indicates a decrease in mechanical strength, while a positive difference indicates an increase in mechanical strength.
[0178] Adhesive No. Dry strength(MPa) Wet strength (MPa) difference 18 4.3 4.7 +9.3%
[0179] In view of the above specific embodiments of the present invention, other modifications and variations will become apparent to those skilled in the art. However, it should be apparent that such other modifications and variations can be implemented without departing from the spirit and scope of the present invention.
Claims
1. A binding resin comprising the reaction product of a carbohydrate reactant, lignin and a polyamine, wherein the carbohydrate reactant is selected from a monosaccharide, a disaccharide or an oligosaccharide, and wherein the polyamine is a primary polyamine selected from a diamine, a triamine, a tetraamine and a pentamine, and wherein the polyamine is H2N-Q-NH2, wherein Q is C1-C 10 Alkyl, cycloalkyl, C1-C 10 heteroalkyl or cycloheteroalkyl, each of which is optionally substituted; and wherein the lignin is provided as a solution, and wherein the weight ratio of carbohydrate to polyamine is in the range of from 1:100 to 100:1, and wherein the weight ratio of lignin to carbohydrate is between 1:100 and 100:1, calculated on a dry lignin and dry carbohydrate basis, and wherein the ratio of dry lignin to dry polyamine is between 1:100 and 100:1, and wherein the amount of lignin in the binding resin is in the range of from 1 wt % to 50 wt %, calculated on a dry lignin and dry binding resin basis.
2. The binding resin according to claim 1, wherein the carbohydrate reactant is a disaccharide.
3. The binding resin according to claim 2, wherein the disaccharide is selected from sucrose, lactose and maltose.
4. The adhesive resin according to any one of claims 1 to 3, wherein the polyamine is selected from 1,6-diaminohexane, 1,5-diamino-2-methylpentane, hexamethylenediamine, polyetheramine, 3-(aminomethyl)-3,5,5-trimethylcyclohexane-1-amine, diethylenetriamine, 1-piperazineethylamine, bis(hexamethylene)triamine, triethylenetetramine and tetraethylenepentamine.
5. The adhesive resin according to any one of claims 1 to 4, wherein the adhesive resin does not contain an epoxy-based crosslinking agent.
6. The binding resin according to any one of claims 1 to 5, wherein the lignin is not chemically modified after it is extracted and separated from the wood.
7. The binding resin according to any one of claims 1 to 6, wherein the weight ratio of carbohydrate to polyamine is in the range from 1:20 to 20:1, preferably in the range from 1:10 to 10:1, most preferably in the range from 1:5 to 5:1, calculated on a dry solids basis.
8. The binding resin according to any one of claims 1 to 7, wherein the weight ratio of lignin to carbohydrates is in the range from 1:40 to 40:1, preferably in the range from 1:20 to 20:1, most preferably in the range from 1:10 to 10:1, calculated on a dry solids basis.
9. The binding resin according to any one of claims 1 to 8, wherein the weight ratio of lignin to polyamine is in the range from 1:50 to 50:1, preferably in the range from 1:20 to 20:1, most preferably in the range from 1:10 to 10:1, calculated on a dry solids basis.
10. A fibrous insulation product comprising the binding resin according to any one of claims 1 to 9 and a fibrous material.
11. The cellulosic insulation product of claim 10, wherein the cellulosic material is selected from the group consisting of glass fibers, mineral fibers, aramid fibers, ceramic fibers, metal fibers, carbon fibers, polyimide fibers, polyester fibers, rayon fibers, and cellulose fibers.
Citation Information
Patent Citations
Binder compositions and associated methods
US20050202224A1
Binders and materials made therewith
US20070027283A1
Method for separating lignin from black liquor
WO2006031175A1
binders
WO2009019235A1